Simultaneous CVD synthesis of graphene-diamond hybrid films - Carvalho, Alexandre F.
An innovation is reported in the synthesis of a hybrid carbon structure resulting from the simultaneous growth of graphene and nanocrystalline diamond (NCD) by the microwave plasma chemical vapor deposition technique. This strategy allows to take advantage of the complementary electronic behavior of each carbon allotrope, a key feature in new nanostructured materials for electronics under the graphene/insulator all-carbon approach. The graphene-diamond hybrid structures were grown on copper and transferred to a glass substrate to be further characterized. Raman analysis puts in evidence the signature of both phases and the high crystallinity of the graphene layer, based on band intensity and width measurements. Raman mapping and SEM observations show a uniform distribution of the NCD clusters, confirmed by AFM/EFM measurements. Additionally, HRTEM analysis permitted to detail the diamond nanocrystalline structure, revealing a close link to the graphene layer on the basis of which a diamond on graphene nucleation mechanism is proposed. (C) 2015 Elsevier Ltd. All rights reserved.